Effect of SGLT-2 inhibitor, dapagliflozin, on left ventricular remodeling in patients with type 2 diabetes and HFrEF - Qianyu Fu; Longhua Zhou; Yuqin Fan; Fenfen Liu; Yuanyuan Fan; Xin Zhang; Li Wang; Lan Cheng (BMC Cardiovascular Disorders, 2023)
Abstract The current study evaluated the effect of SGLT-2 inhibitor, dapagliflozin, on left ventricular remodeling in patients with type 2 diabetes and HFrEF. 60 patients were randomized (1:1) to receive dapagliflozin 10 mg once daily, or placebo double blind for 1 year. Patients underwent transthoracic echocardiography and doppler evaluation prior to dapagliflozin initiation and at 1 year. At 1year, adjusted mean difference versus placebo in change from baseline in LVEF was 2.5% (95% CI: 1.00–4.06, P = 0.002). Adjusted mean difference versus placebo in change from baseline in LVED volume was − 6.0ml (95% CI: -8.07 -−3.87, P<0.001). Adjusted mean difference versus placebo in change from baseline in LVES volume was − 8.1ml (95% CI: -11.07 -−5.14, P<0.001). Similarly, adjusted mean difference versus placebo in change from baseline in LVED diameter was − 1.6 mm (95% CI: -2.67 -−0.62, P = 0.002). Adjusted mean difference versus placebo in change from baseline in VTI was 0.20 cm (95% CI: 0.01–0.38, P = 0.036). Dapagliflozin was well tolerated. Dapagliflozin was associated with significant and clinically meaningful improvement in echocardiographic parameters versus placebo in patients with type 2 diabetes and HFrEF. Registration number and date: ChiCTR2300072707, 21/06/2023.